2022
DOI: 10.1029/2021jd035018
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Resolution Whole‐Atmosphere Model With Resolved Gravity Waves and Specified Large‐Scale Dynamics in the Troposphere and Stratosphere

Abstract: Atmospheric general circulation models (GCMs) are valuable tools to study large-scale atmospheric variability and its sensitivities to external perturbations (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 79 publications
3
79
0
Order By: Relevance
“…One explanation for the model easterly wind bias in the polar winter MLT is that the model omits higher order GWs, and thus the eastward drag caused by these GWs. Other known deficiencies in the existing GW parameterization that may contribute to the easterly wind bias in the model include: the absence of oblique GW propagation (e.g., Sato et al, 2009;Thurairajah et al, 2017Thurairajah et al, , 2020, the need to modify the GW source spectrum (e.g., Liu & Roble, 2002;Pramitha et al, 2020), the need to impose GW sources at all altitudes (e.g., Ribstein et al, 2022) including tropospheric jet exit regions and the stratospheric polar vortex (e.g., Becker et al, 2022;Dörnbrack et al, 2018;Sato & Yoshiki, 2008), and the need to tune GW parameterizations according to simulated tidal variability (e.g., Becker, 2017). Future work will investigate running the model at 0.25° horizontal resolution, following Liu et al (2014), to quantify the sensitivity of the easterly wind bias to model resolution.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the model easterly wind bias in the polar winter MLT is that the model omits higher order GWs, and thus the eastward drag caused by these GWs. Other known deficiencies in the existing GW parameterization that may contribute to the easterly wind bias in the model include: the absence of oblique GW propagation (e.g., Sato et al, 2009;Thurairajah et al, 2017Thurairajah et al, , 2020, the need to modify the GW source spectrum (e.g., Liu & Roble, 2002;Pramitha et al, 2020), the need to impose GW sources at all altitudes (e.g., Ribstein et al, 2022) including tropospheric jet exit regions and the stratospheric polar vortex (e.g., Becker et al, 2022;Dörnbrack et al, 2018;Sato & Yoshiki, 2008), and the need to tune GW parameterizations according to simulated tidal variability (e.g., Becker, 2017). Future work will investigate running the model at 0.25° horizontal resolution, following Liu et al (2014), to quantify the sensitivity of the easterly wind bias to model resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Determine how the polar vortex contributes as a source of primary GWs during strong vortex states. For example, Liu (2017) and Becker et al (2022a) observed/simulated in-situ generation of GWs by a disturbed polar vortex. 9.…”
Section: Figurementioning
confidence: 99%
“…The HIAMCM (HIgh Altitude Mechanistic general Circulation Model) (Becker and Vadas, 2020;Becker et al, 2022) is a new, high-altitude version of the KMCM (Kühlungsborn Mechanistic general Circulation Model). The HIAMCM employs a spectral dynamical core with a terrain-following hybrid vertical coordinate.…”
Section: Hiamcmmentioning
confidence: 99%
“…Nevertheless, the key features of a climate model (topography, simple ocean model, radiative transfer, boundary layer processes, tropospheric moisture cycle) are fully taken into account. Also note that the HIAMCM is currently the only GWresolving whole atmosphere model that can be nudged to reanalysis in the troposphere and stratosphere, allowing for the simulation of observed events (Becker et al, 2022).…”
Section: Hiamcmmentioning
confidence: 99%
See 1 more Smart Citation